IDENTIFICATION OF IRON MINERALIZATION ZONES USING FORWARD MAGNETIC MODELING METHODS IN PELAIHARI – TANAH LAUT REGENCY - Aulia Qorina; Selvi Misnia Irawati; Purwaditya Nugraha; Yoqi Ali Taufan (Engineering Faculty Universitas Lampung, 2026)
Accuracy in identifying the distribution zone of iron ore mineral resources in the Pelaihari area, Tanah Laut Regency, is very important for exploration activities. This study aims to identify the presence of iron ore using magnetic data based on Analytical Signal maps from residual processing and modeling 2D subsurface results to see iron ore mineralization zones. The magnetic method used in this study is a geophysical exploration technique based on measurements of variations in magnetic anomaly intensity in rocks caused by the Earth's magnetic field. Magnetic data underwent magnetic correction, daily correction, and correction according to the International Geomagnetic Reference Field (IGRF) standard to determine the Total Magnetic Intensity (TMI). Based on the results of the study, iron ore mineralization zones were identified at a depth of approximately 10–40 m from the surface with a high susceptibility value of around 0.2 SI. The high residual anomaly response and Analytic Signal values between 23.4–36.0 nT/m indicate a shallow magnetic source localized by ultramafic rocks as the bedrock with a susceptibility value of approximately 0.097 SI at a depth of up to ±150 m, forming a prominent upward bulge. These characteristics indicate significant potential for laterite mineralization.